DARI SAKINAH KE MASLAHAH (Gerakan Keluarga Maslahah Nahdlatul Ulama & Pergeseran Politik Hukum Keluarga di Indonesia) - Abdillah Halim; Ana Indriana (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
The maslahah family movement was initiated by PBNU with certain objectives, first, as part of the effort to present PBNU in the daily lives of NU members, second, an effort to consolidate the movement from below in order to build a better civilization, and third, the development of a good civilization cannot be achieved without the formation of a maslahah family. The legal policy of the sakinah family in its derivatives requires five pillars or principles of relations in the household, namely mitsaqan ghalidza (a firm promise), zawaj (essence and existence in pairs), muasyarah bil ma'ruf (good relations), deliberation, and taradhin (mutually willing or pleasing). The legal policy of the maslahah family movement, if read from the perspective of critical legal theory, will lead us to an understanding of several things. First, the family maslahah movement at a certain level must be encouraged as a political movement, meaning that the family maslahah movement as a social movement must be consolidated in such a way that it directs the government's political policy-making processes so that more and more government political policies support and are compatible with the family maslahah movement. Second, the concept and movement of the family maslahah must accommodate various perspectives and contexts of society. The family maslahah movement, which genealogically comes from the tradition, perspective, and interpretation of NU, requires "objectification" and "universalization" if it is to be developed widely to communities with different religious backgrounds and traditions. Furthermore, the third thing is that the concept and movement of the family maslahah must be open to interdisciplinary academic criticism in order to remain contextual in an era that is constantly changing.